1999
DOI: 10.1016/s0022-5347(05)68794-0
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic Urinary Diversion With Preservation of Erectile and Ejaculatory Function in Men Requiring Radical Cystectomy for Nonurothelial Malignancy: A New Technique

Abstract: The technique of cystectomy with preservation of the vasa deferentia, seminal vesicles, posterior prostate and neurovascular bundles is an excellent option in men with nonurothelial malignancy or another pathological condition that necessitates cystectomy, and in whom preservation of fertility and potency is desirable. All of our patients are fully potent and achieve ejaculation. Even the patient with retrograde ejaculation remains fertile. In terms of practicality semen retrieval from urine is much simpler th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 1 publication
1
48
0
4
Order By: Relevance
“…[29][30][31][32][33] Urethral-sparing RC in females, prostate and seminal vesicle-sparing RC in males have been shown to improve the sexual function. Preservation of these structures reduces the chances of injury to the cavernosal nerves, without any apparent oncological compromise.…”
Section: Ed In Malesmentioning
confidence: 99%
“…[29][30][31][32][33] Urethral-sparing RC in females, prostate and seminal vesicle-sparing RC in males have been shown to improve the sexual function. Preservation of these structures reduces the chances of injury to the cavernosal nerves, without any apparent oncological compromise.…”
Section: Ed In Malesmentioning
confidence: 99%
“…4 In both cases, the neurovascular bundle, the distal sphinteric complex, and the continuity of the vas, seminal vesicles and ejaculatory duct remain undisturbed.…”
Section: Prostate-sparing Techniquesmentioning
confidence: 98%
“…Spitz et al [23] recently reported a small series of fertility-and nerve-sparing cystectomies in four young patients, all of whom had nontransitional cell malignancies. This approach, which involves sparing part of the posterior prostate, seminal vesicles and ejaculatory duct, incorporates a nerve-stimulating approach.…”
Section: Other Uses For Cavernosal Nerve Mapping: Nerve Grafts and Nementioning
confidence: 99%